CONSTRUCTION OF AN EFFECTIVE WAREHOUSE SYSTEM OF THE ENTERPRISE IN THE PROCESSING OF AGRICULTURAL CARGO: Array - Pavlenko, O.; Velykodnyi, D. (Municipal economy of cities (Technical science), 2021)
The article investigates the existing trends and prospects for the development of warehousing services in the system of production and processing of products, which allowed us to form the purpose of the research in this development. The chosen theme is quite topical, because warehousing processes are an integral part of the formation of supply logistics in modern production processes. One of the ways to reduce the cost of goods and services is the efficient use of resources. Ukrainian and foreign scientists have touched many questions concerning the development of the infrastructure component, solutions of optimization problems regarding the process of import-export of goods to the warehouse, but without determining the optimal values ​​of technological parameters of warehousing systems. The technological scheme of operation of the warehouse system of the enterprise LLC "MEGA CRISP» allows to see the whole chain of operations from the moment of arrival of the vehicle with cargo (containers and packaging) to the moment of sending the cargo (finished product) to the recipient; the necessary types of resources involved in these processes are also taken into account. Total costs were chosen as an evaluation indicator of the choice of an efficient supply channel. Relevant parameters of influence are taken into account: intensities of corresponding cargo flows, unit cost of the appropriate work and one hour of work of one worker, time of performance of an appropriate operation, quantity of the involved resources for performance of the appropriate operation and working time of the warehouse during the day. An imitation full-factor experiment was performed, based on the results of which a regression model in linear form with a non-zero coefficient was determined, in which each coefficient indicates the degree of influence of the relevant factor on the performance indicator. The results of determining the economic effect showed that "Variant 2" (increasing the number of workers) is the least expensive, and the level of costs is lower for all series of experiments compared to the basic variant - "Variant 1". The maximum difference is reached in 12217.8 hryvnias at the maximum loading of a warehouse. And when comparing the third and first variants: only at the maximum level of output flow (170 t / h), the third variant will be cheaper by 852.6 hryvnias. The highest level of positive value of the effect among the variants offered is "Variant 2", the level of savings will be 12,217.8 hryvnias per shift.